2022
DOI: 10.1002/ece3.9343
|View full text |Cite
|
Sign up to set email alerts
|

Neutral and adaptive loci reveal fine‐scale population structure in Eleginops maclovinus from north Patagonia

Abstract: Patagonia is an understudied area, especially when it comes to population genomic studies with relevance to fishery management. However, the dynamic and heterogeneous landscape in this area can harbor an important but cryptic genetic population structure. Once such information is revealed, it can be integrated into the management of infrequently investigated species. Eleginops maclovinus is a protandrous hermaphrodite species with economic importance for local communities that are curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…The dynamic and heterogeneous landscape in Patagonia, can harbor an important Population Genetic Structure of Marine Fishes DOI: http://dx.doi.org/10.5772/intechopen.112694 but cryptic genetic population structure using restriction site-associated DNA (RAD) sequencing. In five locations sampled, distributed across a salinity cline from Northern Patagonia, Canales et al [69] identified a spatial structuration with gene flow and spatial selection by environmental association. Neutral loci gave two genetic group meanwhile adaptive loci gave three genetic groups.…”
Section: New Technologies and Future Developmentmentioning
confidence: 99%
“…The dynamic and heterogeneous landscape in Patagonia, can harbor an important Population Genetic Structure of Marine Fishes DOI: http://dx.doi.org/10.5772/intechopen.112694 but cryptic genetic population structure using restriction site-associated DNA (RAD) sequencing. In five locations sampled, distributed across a salinity cline from Northern Patagonia, Canales et al [69] identified a spatial structuration with gene flow and spatial selection by environmental association. Neutral loci gave two genetic group meanwhile adaptive loci gave three genetic groups.…”
Section: New Technologies and Future Developmentmentioning
confidence: 99%
“…Genomic techniques, which generate thousands to millions of polymorphic loci, have increased power for detecting population structure and signals of adaptation, making them particularly attractive for application to marine systems (Waples and Gaggiotti 2006;Bernatchez et al 2017). Indeed, there is a growing number of examples in which genomic approaches detected population structure in marine or fishery species that previously went undetected by using traditional genetic techniques (Nielsen et al 2012;Gaither et al 2015;Ackiss et al 2020;Glass et al 2021;Canales-Aguirre et al 2022;Longo et al 2022), some of which include the identification of genomic structural variants associated with adaptive variation (Benestan et al 2016;Berg et al 2016;Barth et al 2017;Longo et al 2020). Despite these promising results, most assessments for species that are harvested in commercial fisheries do not include genomic insights on stock structure (Bernatchez et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…2021; Canales‐Aguirre et al. 2022; Longo et al. 2022), some of which include the identification of genomic structural variants associated with adaptive variation (Benestan et al.…”
Section: Introductionmentioning
confidence: 99%